2020
DOI: 10.3390/met10010116
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Fatigue Properties of H13 Hot-Work Tool Steels Processed by Selective Laser Melting

Abstract: Currently, selective laser melting (SLM) is gaining widespread popularity as an alternative manufacturing technique for complex and customized parts, especially for hot-work and injection molding applications. In the present study, as the major factors for the failure of H13 hot-work die steels during hot-working, thermal fatigue (TF) properties of H13 processed by SLM and a conventional technique were investigated. TF tests (650 °C/30 °C) were conducted on the as-selective laser melted (As-SLMed), thermally t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…Fig. 10b shows a comparison of tensile strength of H13 steel manufactured by different techniques, including conventional casting methods [18,41,42], SLM [ [1,2,23,28,43]] and SLM þ heat treatment [28,34,41]in both other literatures and this study. Obviously, the ST-600 and ST-700 samples showed a good balance between strength and ductility.…”
Section: Mechanical Propertiesmentioning
confidence: 75%
See 1 more Smart Citation
“…Fig. 10b shows a comparison of tensile strength of H13 steel manufactured by different techniques, including conventional casting methods [18,41,42], SLM [ [1,2,23,28,43]] and SLM þ heat treatment [28,34,41]in both other literatures and this study. Obviously, the ST-600 and ST-700 samples showed a good balance between strength and ductility.…”
Section: Mechanical Propertiesmentioning
confidence: 75%
“…The as-SLMed H13 is usually featured by fine primary grains, cellular structures and carbides [10,17]. However, the resulting mechanical properties are normally unsatisfactory due to the high-volume fraction of retained austenite (15e20%) [15,18] and residual stresses (~1420 MPa) [12,19,20]. Moreover, the ductility is inferior to that obtained by conventional manufacturing techniques [21e23].…”
Section: Introductionmentioning
confidence: 99%
“…Commercial forged H13 steels have been reported to have UTS of 1200–1590 MPa, elongation of 6–9%, and hardness of 46–50 HRC [ 22 , 36 , 37 , 38 ]. Regarding these mechanical properties of commercially forged H13, additively manufactured H13 using the LPBF process did not show significant differences in this study.…”
Section: Resultsmentioning
confidence: 99%
“…They revealed that the direct tempering of H13, showing more dispersal of carbide, resulted in a lower thermal softening than conventional post-HT of H13, which includes a solution treatment before the tempering. Wang et al [ 22 ] investigated the effect of a double-tempering HT on the thermal fatigue properties of H13 manufactured using a selective laser melting (SLM) process, which fully melts the metal powder. The H13 manufactured using the SLM showed a superior thermal fatigue resistance compared to the forged H13 due to its fine microstructure and higher amount of retained austenite.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the elongation of as-SLMed H13 is normally lower than that obtained by conventional methods [ 12 , 13 , 14 ]. It was addressed that the high fluctuation of mechanical properties are mainly a response for the different contents of residual austenite [ 15 , 16 ], high residual stresses [ 17 , 18 , 19 ] and defects [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%